2011
DOI: 10.1037/a0023895
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal respiratory dysfunction and neuropsychological performance at the preschool age: A study of very preterm infants with bronchopulmonary dysplasia.

Abstract: A significant, yet circumscribed, association was demonstrated between neonatal hypoxic risk, in the VP infant, and neuropsychological outcome assessed in the preschool years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
1
15
0
2
Order By: Relevance
“…13,6,7,39 Although BPD may play an important role in the long-term outcomes of preterm infants, our findings show that increased IsoPs between days 14 and 28 are associated with both worse respiratory disease at term equivalent age and with worse neurodevelopmental scores in the first year. OS, therefore, may be a common antecedent to both outcomes instead of early respiratory status directly affecting neurodevelopmental outcomes.…”
Section: Discussionmentioning
confidence: 58%
“…13,6,7,39 Although BPD may play an important role in the long-term outcomes of preterm infants, our findings show that increased IsoPs between days 14 and 28 are associated with both worse respiratory disease at term equivalent age and with worse neurodevelopmental scores in the first year. OS, therefore, may be a common antecedent to both outcomes instead of early respiratory status directly affecting neurodevelopmental outcomes.…”
Section: Discussionmentioning
confidence: 58%
“…Nonoxygen-dependent children with BPD have been reported to catch up developmentally at 2 years of age, whereas those initially discharged home on oxygen have been reported to catch up by 4 years of age, 114 but infants who required mechanical ventilation at 36 weeks PMA were 6 times more likely to have quadriparesis compared with infants who required only supplemental oxygen at 36 weeks PMA. 115 Close neurodevelopmental follow-up can provide parents with reassurance and education on appropriate developmental milestone attainment, specific to the child’s chronologic age and degree of prematurity.…”
Section: Transitional and Postdischarge Care Of Infants With Sbpdmentioning
confidence: 99%
“…These risk factors include intra-uterine growth restriction, 15,16 severe infections, [17][18][19] and bronchopulmonary dysplasia. [20][21][22] Intra-uterine growth restriction Intra-uterine growth restriction has long been identified as a risk factor for a wide variety of developmental problems in term and preterm children. 23 In particular, children born very preterm with intra-uterine growth restriction are at increased risk, not only for motor problems but also for behavioural and cognitive impairments.…”
Section: Specific Risk Factors For Impaired Fine Motor Skills At Schomentioning
confidence: 99%
“…20 It has been reported that impaired fine motor skills are related to the severity of bronchopulmonary dysplasia, reflected in the duration of oxygen treatment. 21 Treatment with systemic corticosteroids of children with bronchopulmonary dysplasia, in particular dexamethasone, is another risk factor for development of severe motor disorders such as CP. 25 Recently, data have been presented on a case-control study of preterm children with bronchopulmonary dysplasia who had been treated with dexamethasone.…”
Section: Bronchopulmonary Dysplasia and Dexamethasone Treatmentmentioning
confidence: 99%